Genetic diversity of Gibsmithia hawaiiensis complex (Dumontiaceae, Rhodophyta) - Gabriel, Daniela (2017)
ABSTRACT: The genus Gibsmithia was erected to accommodate a species with the peculiar combination of gelatinous lobes rising from cartilaginous stalks. Based on G. hawaiiensis from Hawaii, it remained monotypic for over 20 years, when three additional species were described from Australia. G. hawaiensis is unique for its furry appearance due to cortical filaments beyond the surface. Gibsmithia have been reported from the Indian Ocean and central and western Pacific, with G. hawaiensis having the widest distribution. Genetic studies based on COI, rbcL and UPA, reveal that G. hawaiiensis is monophyletic with nine distinct species sharing a similar habit. G. hawaiiensis complex exhibits high genetic diversity in Indomalaysia region, with different species presenting genetically variable populations. Species restricted to isolated region as Hawaii or the Red Sea comprises genetically conserved populations. Four of those cryptic species can be distinguished based on characters previously regarded as morphological plasticity: the generitype and the new species G. eilatensis, G. indomalayensis and G. lata distributa. Because specimens of the other species are only available dried onto herbarium paper or in silica-gel, their reproductive characters can not be characterized. New reports of the complex are given to Madagascar, Europa Island, the Red Sea and Guam, and also to new regions of Malaysia, Indonesia, the Philippines and the French Polynesia.